Organic Laser Dyes: Deep‐Red Lasing and Amplified Spontaneous Emission from Nature Inspired Bay‐Annulated Indigo Derivatives (Advanced Optical Materials 2/2020). Issue 2 (17th January 2020) - Shukla, Atul; Wallwork, Nicholle R.; Li, Xin; Sobus, Jan; Mai, Van T. N.; McGregor, Sarah K. M.; Chen, Kay; Lepage, Romain J.; Krenske, Elizabeth H.; Moore, Evan G.; Namdas, Ebinazar B.; Lo, Shih‐Chun
Abstract : Evan G. Moore, Ebinazar B. Namdas, Shih‐Chun Lo and co‐workers (article number 1901350 ) discover a new class of solution processable organic semiconductor laser dyes with deep‐red emission. These dyes exhibit high photoluminescence quantum yields and low amplified spontaneous emission (ASE) thresholds. Their use of a mixed host of 1, 3‐bis( N ‐carbazolyl)benzene (mCP) and 2‐hydroxyphenylbenzothiazole (HBT) not only leads to efficient cascade energy transfer, but significantly enhances the photostability of the films thanks to much lower heat dissipation in the chromophores.